Protein ubiquitination in T cell development - Zhong, Ting; Lei, Kang; Lin, Xiaoxi; Xie, Zhiguo; Luo, Shuoming; Zhou, Zhiguang; Zhao, Bin; Li, Xia (Frontiers in Immunology, 2022)
As an important form of posttranslational modification, protein ubiquitination regulates a wide variety of biological processes, including different aspects of T cell development and differentiation. During T cell development, thymic seeding progenitor cells (TSPs) in the thymus undergo multistep maturation programs and checkpoints, which are critical to build a functional and tolerant immune system. Currently, a tremendous amount of research has focused on the transcriptional regulation of thymocyte development. However, in the past few years, compelling evidence has revealed that the ubiquitination system also plays a crucial role in the regulation of thymocyte developmental programs. In this review, we summarize recent findings on the molecular mechanisms and cellular pathways that regulate thymocyte ubiquitination and discuss the roles of E3 ligases and deubiquitinating enzymes (DUBs) involved in these processes. Understanding how T cell development is regulated by ubiquitination and deubiquitination will not only enhance our understanding of cell fate determination via gene regulatory networks but also provide potential novel therapeutic strategies for treating autoimmune diseases and cancer.